Race and Social Problems: Restructuring Inequality - Bangs, Ralph (Springer, 2015)
As much as Americans believe in the promise of an egalitarian, color-blind society, the reality is far from that ideal. People of color consistently lag behind their white counterparts in key quality-of-life areas. Despite many significant gains, widespread structural inequalities continue to exist and thrive.